Analisis Fungsi-Fungsi Manajemen dalam Pelayanan Pasar Sentral Baranti - Dinda Zalza; Nurjannah Nonci; Sandy Lubis; Ahmad Mustanir (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the implementation of management functions in public service delivery at Pasar Sentral Baranti, Sidenreng Rappang Regency. The focus of the study includes three main functions: organizing, actuating, and controlling. This research employs a qualitative descriptive approach. Informants were selected using purposive sampling, involving the head of the market management unit, market officers, traders, and visitors. Data were collected through in-depth interviews, observation, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The results show that the implementation of management functions has not been optimal. The organizing function is characterized by unclear task distribution, the actuating function is not consistently implemented due to low work discipline, and the controlling function remains weak due to irregular supervision. In addition, sociocultural factors, such as informal relationships between officers and traders, influence the consistency of rule enforcement. This study concludes that the effectiveness of public service delivery is determined not only by formal structures but also by the organization’s ability to manage social dynamics adaptively.